IMPLEMENTASI NILAI-NILAI FILSAFAT HUKUM DALAM PEMBENTUKAN HUKUM DI INDONESIA - Almusradin Adha; Rumainur (INTELIGENSIA MEDIA, 2023)
Legal philosophy in Indonesia has the biggest role in the formation of law in Indonesia. Pancasila as a source of law implies the entirety of regulations and laws, starting from our constitution and all regulations apart from our constitution, of course, placing Pancasila as the basis and foundation of the law. Pancasila is the Indonesian legal system. Therefore, Pancasila is not only known as a philosophy but also known as written law in Indonesia which contains living laws. The problem is how big is the role of Legal Philosophy in influencing the formation of the legal system in Indonesia. This question must be very important to answer. The author tries to examine this problem with normative law in the legal method. The approach taken by the author is taken from several books that contain related problems.